Silicon Fertilization in Sugarcane Drought-Contrasting Cultivars Subjected to Water Deficit at the Ripening Phase - Sartori Camargo, Mônica; Baltieri, Gustavo Jonas; dos Reis, André Rodrigues [UNESP]; Pereira, Hamilton Seron; de Almeida Silva, Marcelo [UNESP] (Springer Nature, 2023)
Silicon (Si) could contribute to maintaining nutrient uptake, above-ground and root system biomass, enhancing sugar yield in sugarcane under water deficit at the ripening phase, but results are still scarce. This study aims to determine whether water deficit during the ripening phase causes deleterious effects on the biomass of green leaf, straw, stalk, and root system, nutrient uptake, and sugar accumulation of two drought-contrasting sugarcane cultivars, and whether Si alleviates these effects. An experiment was conducted in pots under greenhouse conditions using a randomized factorial design with two sugarcane cultivars (RB86-7515; RB85-5536), two Si rates (equivalent to 0 and 1000 kg ha−1 Si) as silicate, and the absence (well-watered, WW) or presence of water deficit (WD) during the ripening phase. There was an independent effect of water deficit, cultivar, and Si in soil on plant results. Water deficit decreased concentrations of Si, Ca, Fe, and B in leaves, leaf biomass by 19%, and sugar content by 27%. RB85-5536 showed the highest concentrations of Si, Ca and lower leaf biomass. Si increased soluble Si, base saturation in soil, Si, and Mg in plant, and sugar by 30%, and reduced Fe, and B in the root, straw by 7.3%, stalk biomass by 9.8%. The effects of water deficit were not intense at the ripening phase and caused decreased leaf biomass and enhanced sugar accumulation. Si, in turn, contributed to decreased straw biomass because of Si deposition, maintenance of green leaves, and increased sugar production with or without water deficit.
Keywords: Biomass; Nutrient; Saccharum spp; Silicate; Soil; Sugar